Combinatorial low-volume synthesis of well-defined polymers by enzyme degassing - Chapman,R; Gormley,AJ; Stenzel,MH; Stevens,MM (Angewandte Chemie-International Edition, 2016)
The synthesis of well-defined polymers in a low-volume, combinatorial fashion has long been a goal in polymer chemistry. Here, we report the preparation of a wide range of highly controlled homo and block co-polymers by Enz-RAFT (enzyme-assisted reversible addition–fragmentation chain transfer) polymerization in microtiter plates in the open atmosphere. The addition of 1μm glucose oxidase (GOx) to water/solvent mixtures enables polymerization reactions to proceed in extremely low volumes (40μL) and low radical concentrations. This procedure provides excellent control and high conversions across a range of monomer families and molecular weights, thus avoiding the need to purify for screening applications. This simple technique enables combinatorial polymer synthesis in microtiter plates on the benchtop without the need of highly specialized synthesizers and at much lower volumes than is currently possible by any other technique.